TRIM31: A molecule with a dual role in cancer - Guo, Yafei; Lin, Ping; Hua, Yimin; Wang, Chuan (Frontiers in Oncology, 2022)
Tripartite motif (TRIM) 31 is a new member of the TRIM family and functions as an E3 ubiquitin ligase. Abnormal TRIM31 expression leads to a variety of pathological conditions, such as cancer, innate immunity diseases, sepsis-induced myocardial dysfunction, cerebral ischemic injury, nonalcoholic fatty liver disease and hypertensive nephropathy. In this review, we comprehensively overview the structure, expression and regulation of TRIM31 in cancer. Moreover, we discuss the dual role of TRIM31 in human cancer, and this dual role may be linked to its involvement in the selective regulation of several pivotal cellular signaling pathways: the p53 tumor suppressor, mTORC1, PI3K-AKT, NF-κB and Wnt/β-catenin pathways. In addition, we also discuss the emerging role of TRIM31 in innate immunity, autophagy and its growing sphere of influence across multiple human pathologies. Finally, a better understanding of the dual role of TRIM31 in cancer may provide new therapeutic strategies aimed at inhibiting the cancer-promoting effects of TRIM31 without affecting its tumor suppressor effects.